FOLLOW-UP RESPONSES TO REFUSALS BY INDONESIAN LEARNERS OF ENGLISH AS A FOREIGN LANGUAGE - Muniroh, Dian (Universitas Pendidikan Indonesia, 2013)
Abstract: The study is aimed at investigating strategies of follow-up responses torefusals performed by Indonesians learning English as a foreign language. Havingknown that his/her desire or want is refused by his/her hearer, a speaker may providea follow-up response to the refusal to maintain the flow of a talk exchange. This actmay also mitigate the tension and is able to prevent the speaker from being consideredimpolite or non-cooperative. The study involves 20 students of the English EducationDepartment of Indonesia University of Education. The data were collected throughDiscourse Completion Tests (DCTs). The collected data were then analyzed by usingthe framework proposed by Searle (1969), Blum-Kulka et al. (1989), and Aziz (2000).It is found that the respondents manifest the follow-up responses in a number of ways,which can be categorized as request, acceptance, apology, promise, refusal, and passivecomment. These responses contain some strategies. While the category of requestand refusal are manifested in six and two strategies respectively, the categories ofacceptance, apology, promise, and passive comment are not further divided into finercategories because they only consist of illocutionary force indicating devices (IFIDs).This study concludes that an act of providing a follow-up response cannot be separatedfrom the speaker’s attempt to maintain harmony in communication.